Hubungan Usia, Paritas, dan Tingkat Pendidikan dengan Kehamilan Tidak Diinginkan Pada Pasangan Usia Subur di Surabaya - Shintya Fitri Ayu Purborini; Novela Sanderina Rumaropen (Universitas Airlangga, 2023)
Background: There are many women in the world who have experienced pregnancy every year. The number of pregnancy in developing countries is 185 million and as many as 86 million of pregnancy that occur worldwide. Several studies explain that age, parity, and level of education are factors in the occurrence of unwanted pregnancy. Objective: To determine the relationship between age, parity, and education level with unwanted pregnancy in fertile age couples Methods: This research was an analytical study using a quantitative approach with a Case Control design. The population used in this study was a couple of childbearing age aged 15-45 years with a sample size of 50 couples of fertile age couples. Results: In this study, it was found that the level of education did not have a significant relationship with the risk of unwanted pregnancy. Meanwhile, the number of children also did not have a significant relationship with the risk of unwanted pregnancy. A total of 17 respondents with a percentage of 48.6% aged 20-35 years experienced unwanted pregnancy. Conclusion: Age, education level, and parity are factors that can affect the occurrence of unwanted pregnancies in couples of childbearing age. The ideal age for pregnancy is the age of 20-35 years because the reproductive organs of the prospective mother are fully formed.